Effects of Replacing Protein of Fishmeal with Protein of Poultry By-product Meal on Growth Performance, Body Composition, Liver Histological Changes and Selected Serum Parameters of Nile tilapia - Mahmoud, Rania E.; Gadallah, Hossam; Orma, Ola A. (Journal of Advanced Veterinary Research, 2023)
This research evaluated the viability of completely and partially replacing the protein of fishmeal (FM) with the protein of poultry by-product meal (PBM) for juvenile Nile tilapia fish. One hundred and eighty unsexed Nile tilapia fish have been randomly assigned to four treatment groups, with three replicates including 15 Nile tilapia fish in each replicate stocked in 12 glass aquaria for nine weeks. PBM incorporation levels in the diet at 50% (G2), 75% (G3), and 100% (G4) protein content of fish meal substituted for the fish meal-based control diet have been compared (100% fish meal, G1). The final body weight (FBW), body weight gain (BWG), specific growth rate (SGR), and protein efficiency ratio (PER) varied considerably across all treatment groups (p> 0.05). FBW, BWG, SGR, and PER were improved for fish fed PBM and were superior in the high level of PBM (G4). However, the morphometric indexes do not significantly differ (p > 0.05). Fat & ash % of body composition was higher in all groups containing PBM in particular (G4) as compared with the control one. In conclusion, it can be said that a full replacement PBM protein for FM protein is tolerable in Nile tilapia fish. Several changes in biochemical parameters and antioxidant status markers were observed. The histological exam of the liver in all groups that contained PBM revealed no abnormalities. However, replacing 75% of the protein of FM with PBM’s protein is the optimal degree in term of maintaining meat quality and some of the blood parameters. Â